Opioid Misuse and the Undertreatment of Pain: Striking a Balance - Goshua, Anna (The Meducator, 2014)
In June of this year, Health Canada put forth its proposal to render high-risk drugs tamper-resistant.1 This would entail chemical modifications designed to increase resistance to crushing, chewing, cutting, and dissolution of the tablets. The primary targets of this policy were prescription opioid medications used to manage acute and chronic pain. Recent studies have demonstrated an alarming prevalence of the misuse of these drugs. In Ontario alone, opioid medication abuse is responsible for the death of 1 in 170 people each year.2 An additional 1 in 8 deaths in individuals aged 25-34 can be attributed to the same cause.2 Although some acknowledge this tentative step taken by the federal government to address the rapidly escalating drug crisis as promising, many feel that this action is insufficient. Moreover, while more can be done to address the issue at hand, it is essential to avoid the stigmatization of administering narcotics. Otherwise, patients who truly need these drugs would be deprived of a satisfactory quality of life.